Problematika Kebijakan Penegakan Hukuman Pidana Mati Untuk Koruptor Pada Masa Pandemi Corona Virus Disease 2019 (Covid-19) - Wildan Tantowi; N.G.A.N Ajeng Saraswati; Viola Sekarayu Gayatri (UIR Press, 2021)
This research examines the problems arising from the criminal law policy of imposing the death penalty for corruptors during the Covid-19 pandemic. C. Law Number 31 of 1999 which has been amended by Law Number 20 of 2001 concerning the Eradication of Corruption Crimes is one of the weapons to fight corruption in Indonesia, especially during the Covid-19 pandemic as a national non-natural disaster which has been a serious concern of the government. In the event of corruption cases occur during the Covid-19 pandemic, such criminal cases should be tackled in an extraordinary and special way because the impact of Covid-19 pandemic has affected all sectors of life, one of which is the economy. Considering the Covid-19 pandemic, it is appropriate if Indonesia is currently categorized under certain conditions. It means that this condition implies that if a criminal act of corruption occurs during the Covid-19 pandemic, law enforcers can prosecute or impose a death penalty for corruption perpetrators as stipulated in Article 2 paragraph (1) and (2) of the Corruption Eradication Law. This research used the normative legal method which is carried out through literature study with the aim of writing the article to find out what weaknesses can lead to juridical problems with the enforcement of the death penalty against corruptors in Indonesia and to analyze the urgency of criminal law policy n the imposition of the death penalty for corruptors during the Covid-19 pandemic.